Assessment and analysis of financial literacy campaigns from financial institutions for Small- and Medium Size Enterprises (SME's) in Colombia - Valentina Rodríguez Pasmi\~no; Claudia Nelly Berrones-Flemmig (IU Internationale Hochschule, 2023)
The lack of financial literacy in SMEs is one of the main obstacles to SMEs finance (Zavatta, 2008). This problem is even greater in developing countries where the informal economy, the low levels of education and the low bancarization rates are known to be high in this region. One of the relevant trends in SME Finance are innovative financial instruments in "capacity building" mainly financial literacy campaigns (or financial education offerings) from financial institutions (Imanbaeva et al., 2017). The main research question of the present study is: Do financial literacy campaigns (or financial educational offerings) provide an adequate level of financial education for SMEs in Colombia? This research project was carried out applying a qualitative methodology. The primary data has been obtained through different types of 11 indepth interviews from the perspective of the financial institutions and also from Chambers of Commerce that provide the trainings. From the assessment and analysis of the financial literacy campaigns, the main results show that the programs that are designed for rural areas of the country do not have all the necessary components that the OECD recommends for a person to be considered financially educated. The financial education offerings carried out in the big cities (offered by the Banco de Bogota, the Chamber of Commerce of Bogota and Cali) provide SMEs with key mechanisms in financial education of great value, according with the components that the OECD recommends. Other important aspects from the results show that the financial education trainings are very short, so that it is not possible to cover all the required topics from the OECD to consider someone financial educated. Furthermore, several participants of the financial trainings are not able to finish due to her/his responsibilities as entrepreneur. Besides, for most of the offerings, there is not an impact evaluation (post-evaluation) about the effect of the trainings regarding the application of the knowledge in financial matters.
Keywords: M; O; 650; SME Finance; financial literacy campaigns; financial education; financial inclusion